Poland and Germany – media pictures of the 1990s exemplified by „Gazeta Zachodnia – Westzeitung” (Economic and Political Thought, 2016)
The article attempts to present the role of mass media in internationalcommunication within the specific situation of the Polish-German borderlandimmediately after 1989. The analysis is based on press releases in GazetaZachodnia – Westzeitung, a joint venture of Wrocław based publishing houseFo-Press and Dieter Breuer Verlag, a German publisher from Wiesbaden,published from April 1990 till August 1995. The periodical, having been a privateenterprise, is one of the first independent cross-border media projectsafter the political system transformation in Poland to fulfil the postulates ofinternational editorial boards, cross-border impact and distribution range,and bilingualism in the content of communication, in this case focused onPolish-German issues. The periodical exemplifies the process of the revivalof independent journalism in Poland after 1989. Although, the paper didnot survive, its functioning was inextricably linked to the transformationalchanges in Poland – it played a crucial role in creating general opinions aboutthe Germans in Poland and about the Poles in Germany.